The Oxford handbook of Irish politics - Farrell, David M. 1960-; Hardiman, Niamh (Oxford handbooks online, 2021)
Ireland has enjoyed continuous democratic government for almost a century, an unusual experience among countries that gained their independence in the 20th century. But the way this works in practice has changed dramatically over time. Ireland's colonial past had an enduring influence over political life for much of the time since independence, enabling stable institutions of democratic accountability, while also shaping a dismal record of economic under-development and persistent emigration. More recently, membership of the EU has brought about far-reaching transformation across almost all aspects of Irish life. But if anything, the paradoxes have only intensified. This handbook provides comprehensive coverage of Irish politics and society